Anthropogenic CO2 in the ocean - Peng, Tsung-Hung (Scientia Marina, 2005)
The focus of this review article is on the anthropogenic CO2 taken up by the ocean. There are several methods of identifying the anthropogenic CO2 signal and quantifying its inventory in the ocean. The ?C* method is most frequently used to estimate the global distribution of anthropogenic CO2 in the ocean. Results based on analysis of the dataset obtained from the comprehensive surveys of inorganic carbon distribution in the world oceans in the 1990s are given. These surveys were jointly conducted during the World Ocean Circulation Experiment (WOCE) and the Joint Global Ocean Flux Study (JGOFS). This data set consists of 9618 hydrographic stations from a total of 95 cruises, which represents the most accurate and comprehensive view of the distribution of inorganic carbon in the global ocean available today. The increase of anthropogenic CO2 in the ocean during the past few decades is also evaluated using direct comparison of results from repeat surveys and using statistical method of Multi-parameter Linear Regression (MLR). The impact of increasing oceanic anthropogenic CO2 on the calcium carbonate system in the ocean is reviewed briefly as well. Extensive studies of CaCO3 dissolution as a result of increasing anthropogenic CO2 in the ocean have revealed several distinct oceanic regions where the CaCO3 undersaturation zone has expanded.